Study of clinical and epidemiological profile of thyroid swelling - Chandrashekhar Srivastava; Anand Saxena (International Journal of Medical Research and Review, 2015)
Introduction: Thyroid swelling remains a problem of enormous magnitude all over the world. The problem in clinical practice is to distinguish reliably the few malignant tumors from the many harmless nodules so that a definitive preoperative tissue diagnosis of the malignancy allows planning of appropriate surgery and relevant patient counseling. FNAC is reliable, safe and accurate method as a first line of evaluation in thyroid swelling before the surgery.Material And Methods : The present study was conducted in Department of Medical College. It included Cross sectional study of cytomorphology of fine needle aspiration cytology material of 156 patients presenting with thyroid nodule in the Department. Information about the clinical presentation, treatment modality and presence or absence of malignancy was collected in a proforma and was analyzed. Statistical tests employed are tests of proportion, tests of percentage, Student’s t-test and Fisher’s exact test.Results : The commonest age group affected was 51-60 yrs. The female patients (69.8%) outnumbered the male patients (30.1%). The cytomorphological analysis of 156 patients revealed 10 cases of neoplastic lesions. Maximum number (122) of patients was suffering with goiter followed by lymphocytic thyroiditis (12) and nodular disease (8). Amongst the malignant cases six cases were of papillary carcinoma and six cases of follicular carcinoma.Conclusion : FNAC is a simple, safe and cost-effective diagnostic modality in the investigation of thyroid disease with high specificity and accuracy. We concluded that FNAC diagnosis of malignancy is highly significant. A benign FNAC diagnosis should be viewed with caution as false negative results do occur and these patients should be followed up and any clinical suspicion of malignancy even in the presence of benign FNAC requires surgery. So, final diagnosis and treatment pattern should be based upon histopathology.